KEBIJAKAN PIDANA ALTERNATIF KERJA SOSIAL TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA - Islah Islah (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The kids had dared to do criminal acts not only as a large area of the city, but also has up to remote corners of the region. With children as perpetrators of crime adds to the problems facing especially in the overthrow of pidananya, because on one side to implement the provisions of the applicable legislation and on the other hand protect the perpetrators of the continuation of his future as the nation's next generation. On that basis, the required accuracy and the judge in taking policy consideration to the determination of the verdict that will overthrow against the perpetrators of the crime are still children. In the matter of the determination of the verdict against a rogue or a child who commits a criminal act in addition to judge received reports the results of research of civic mentors, judges are also obliged to pay attention to the types of crime that kids do, what is the motive and purpose of criminal acts, as well as the weight of the ringannya errors committed by the child.Keyword: criminal policy, the perpetrator of a criminal offence